Live streaming: self-presentation and interaction practices embedded in daily life - Xiang, Yangchun (Frontiers in Communication, 2025)
The article aims to explore the potential trajectory of live streaming entering users’ daily lives in the era of mobile internet, as well as the social roles it plays in users’ practical lives. The article adopts a practical approach to media research, conducting semi-structured in-depth interviews with 10 streamers and 10 viewers, and performing online participant observation based on ethnography of the live streaming of the interviewed streamers. The findings reveal that advancements in communication technology empower users, facilitating the integration of live streaming into daily life and reshaping lifestyles. In a context where everything can be streamed, the pursuit of user values becomes an intrinsic driving force for participation in live streaming. Additionally, the interactions built around live streaming have transcended traditional notions of virtual socialization, evolving into practical interaction practices. The study concludes that live streaming has become a new mode of living for people, with the logic of streaming embedded in daily actions, endowing individuals with an imagination of fame and creating rich social realities.